1969
DOI: 10.5254/1.3539273
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Vulcanized and Unvulcanized SBR/BR Blends

Abstract: Mainly from the temperature dependence of transitions in dynamic modulus, loss tangent, and dielectric loss, associated with microbrownian motions of main chains, it was concluded that blends of NR and BR are microheterogeneous and those of SBR and BR are almost microhomogeneous. Furthermore, even SBR/BR blends tended to be heterogeneous if the styrene content in SBR was increased. On the other hand, unvulcanized SBR/BR blends have been reported to be heterogeneous from observation of phase contrast micrograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In contrast, interfacial bonding in chlorobutyl/polydiene blends has been reported only in the presence of efficient thiuram disulfide and thiuram tetrasulfide vulcanization systems [100]. With less disparate combinations of elastomers (i.e., SBR/BR and NR/BR), Yoshimura and Fujimoto [87] and Corish [58] have demonstrated that the development of interphase cross-linking causes a merging of the dynamic mechanical loss peaks characteristic of the individual polymers. In other investigations [101], co-cross-linking in EPDM/CR blends has been attributed to the independent consumption of differing curatives in each rubber phase.…”
Section: Distribution Of Soluble Compounding Ingredientsmentioning
confidence: 99%
“…In contrast, interfacial bonding in chlorobutyl/polydiene blends has been reported only in the presence of efficient thiuram disulfide and thiuram tetrasulfide vulcanization systems [100]. With less disparate combinations of elastomers (i.e., SBR/BR and NR/BR), Yoshimura and Fujimoto [87] and Corish [58] have demonstrated that the development of interphase cross-linking causes a merging of the dynamic mechanical loss peaks characteristic of the individual polymers. In other investigations [101], co-cross-linking in EPDM/CR blends has been attributed to the independent consumption of differing curatives in each rubber phase.…”
Section: Distribution Of Soluble Compounding Ingredientsmentioning
confidence: 99%
“…However, immiscible IR (polyisoprene)/NR (natural rubber) blends are used for improved wet-skid resistance. [1][2][3][4] The low rolling resistance of tire treads composed of miscible SBR/BR blends is typically achieved using chemically coupled silica as reinforcing filler instead of the more traditional physically coupled carbon black. 5 The SBR type is a solution-polymerized SBR (S-SBR) with approximately 50% of butadiene content in the 1,2-vinyl configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the loss tangent (tan δ) of uncured samples of SBR/BR blends as a function of temperature3 show that two peaks appear related to the glass transition of each phase. After the blend has been vulcanized a unique peak is obtained, and it is stated that the blend may function as a one‐phase system 3, 4. These facts suggest that the two‐phase system is liable to change to a homogeneous system when crosslinking is produced.…”
Section: Introductionmentioning
confidence: 99%